The efficacy of a porcine collagen matrix in keratinized mucosa width augmentation: a 10-year follow-up clinical prospective study - Mattia Manfredini; Pier Paolo Poli; Pierluigi Guerrieri; Mario Beretta; Carlo Maiorana (SpringerOpen, 2023)
Abstract Purpose The aim of the present study was to evaluate the long-term effectiveness of a xenogeneic collagen matrix (CM) in pre-prosthetic augmentation of the keratinized mucosa width (KMW) at implant sites. Methods All of the patients with localized implant-supported rehabilitation previously treated with vestibuloplasty and KMW augmentation with a non-cross-linked porcine CM were recalled. KMW was measured clinically in an apico-coronal direction from the mucogingival junction to the mucosal margin at the prosthetic zenith of each crown. Measurements were performed clinically by means of a PCP-UNC15 periodontal probe and rounded to the nearest mm. KMW values recorded at 1 year, 5 and 10 years from the soft tissue augmentation procedure were compared using a one-way repeated-measures ANOVA with Bonferroni multiple comparison post-hoc analysis. The level of significance was set at 0.05. Results Measurements were conducted on 13 patients. All implants were in function with no signs of biological complications. All except one implant site showed KMW ≥ 2 mm. KMW decreased significantly from 1 year (3.33 ± 1.11 mm) to 5 years (2.77 ± 0.92 mm) (p = 0.001), and finally remained stable from 5 to 10 years (3.2 ± 0.99 mm) (p = 0.607). From a visual aspect, peri-implant soft tissues were characterized by a good texture and color blending compared to the adjacent teeth, highlighting good integration of the remodeled tissues and stability of the esthetic result. Conclusions The use of a CM in pre-prosthetic soft tissue augmentation at implant sites has proven to be effective in obtaining and maintaining at least 2 mm of KMW around dental implants over a follow-up of 10 years.